THE ROLE OF YOUTH IN THE WORLD’S DEVELOPMENT AND POST-WAR REHABILITATION PROGRAMS IN UKRAINE - MANTSUROV, Igor; STIEGLER, Nancy; KHRAPUNOVA, Yana; BARVINOK, Alina (Journal of European Economy, 2022)
The article contains results of the scientific study of the research in several post-war and post-conflicts countries performed by an international team. It is devoted to the generalization of the youth policy experience in terms of solutions to economic and social problems provoked by war conflicts. Adolescents and youth, as a subject of study, in such a post-war situation are considered as important agents and actors in this process. Many young people are not only among the most vulnerable groups affected by armed conflict, poverty, unemployment, they are also the generation that will reach adulthood during the realization of the Sustainable Development Goals (SDGs) 2030 Agenda. In addition to the sustainable development goals, policymakers must not neglect to prioritize the needs of young people and make room for them to carry the next development agenda forward. Young people should be involved in all aspects of the process. Only through meaningful representation by and collaboration with youth will it be possible to move away from an entrenched mindset of delivering basic services to youth towards an approach that empowers young people and enables them to realize their potential with special attention to the conditions of countries that suffered from the armed conflicts. The article offers a number of recommendations on improvement and development of the youth policy in Ukraine as a country that was subjected to a brutal attack by the russian army, an occupation of part of its territory, destruction of the economic and social infrastructure, emergence of a large number of refugees and internally displaced persons, primarily those young and economically active. This paper is addressed to demographers, economists, sociologists and experts in state administration and social policy. JEL: J13, I38, H56, Q56.